Pengembangan Kurikulum di SMP Bunga Matahari Internasional School (BMIS): Analisis pada Pembelajaran PAI - Tahmi Dillah; Zulfatmi Zulfatmi (Tadabbur: Jurnal Peradaban Islam, 2022)
The development of curriculum is an attempt to find out how to plan and organize the objectives, content, and learning materials as well as the methods used as guidelines for the implementation of learning activities in accordance with developments and needs to achieve certain goals in an institution. The subject of the research in this study is the curriculum at SMP Bunga Matahari International School (BMIS). Descriptive analysis research employs data collection techniques such as observation and interviews. The analysis is divided into three stages: data reduction, data presentation, and conclusions. The results of the research showed that the renewal carried out by SMP Bunga Matahari International School (BMIS) was developed by developing the 2013 curriculum and integrating it with the Pearson curriculum. First, the emphasis on development lies in linking learning material to the application of everyday life and situations that are happening. Second, learning methods that lead to learning with experience or practice Therefore, students will be able to absorb their knowledge to the maximum.